THYROID-ASSOCIATED ORBITOPATHY IN HASHIMOTO’S THYROIDITIS: A RARE AUTOIMMUNE OVERLAP - Pawa, Leily D.; Wafa, Syahidatul; Tahapary, Dicky L. (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Thyroid-Associated Orbitopathy (TAO), or Graves’ Orbitopathy (GO), is an immune-mediated inflammatory disorder of the orbit most commonly associated with hyperthyroidism in Graves’ disease. It is primarily driven by TSH receptor antibodies (TRAb), which stimulate orbital fibroblasts and induce tissue remodelling. In contrast, Hashimoto’s thyroiditis is characterized by gland-destructive autoimmunity, with elevated anti-thyroid peroxidase (TPO) antibodies and progressive hypothyroidism. The occurrence of GO in patients with overt hypothyroidism due to Hashimoto’s thyroiditis is rare and represents a unique overlap of autoimmune thyroid diseases. CASE We present the case of a 56-year-old male with no prior history of thyroid disease who presented with progressive, bilateral eye discomfort, photophobia, eyelid swelling, and intermittent diplopia over the preceding eight months. He also reported experiencing fatigue, cold intolerance, dry skin, myalgia, weight gain, and constipation. The patient’s medical history included hypertension, and he was an active smoker; both are known risk factors for orbitopathy. Physical examination revealed eyelid lag, dry skin, and bilateral exophthalmos. His Clinical Activity Score (CAS) indicated active Graves’ orbitopathy (GO). No goitre or tremor was noted. Thyroid function tests confirmed overt hypothyroidism (TSH 19.515 µIU/mL; FT4 0.59 ng/dL), with significantly elevated anti-thyroid peroxidase (anti-TPO) antibodies (9,307.99 IU/mL) and borderline-positive TSH receptor antibodies (TRAb) (1.85 IU/L). Thyroid ultrasound demonstrated reduced thyroid volume and heterogeneous echotexture, consistent with Hashimoto’s thyroiditis. Orbital computed tomography (CT) showed bilateral rectus muscle thickening, further supporting the diagnosis of Graves’ orbitopathy. Clinical improvement was observed following treatment with levothyroxine and selenium. CONCLUSION This case underscores the concept of autoimmune thyroid disease existing on a spectrum, wherein features of both Hashimoto’s thyroiditis and Graves’ disease can coexist. Early recognition of this overlap is crucial for accurate diagnosis, appropriate treatment guidance, and prevention of long-term ocular complications.